Analisis Kesiapan Pembangunan Smart City Daerah Studi Kasus: Kabupaten Temanggung - Ari Fahrina (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
Abstract The development of technology in every aspect of human life, encouraging the emergence of new innovations. One of the uses of technology in government agencies is a smart city. Smart city aims to maximize the utilization of technology that support the improvement of services to the community. Temanggung regency is one of regencies which was selected in the program of the Gerakan Menuju 100 Smart City. This study aims to determine the level of readiness of the government of Kabupaten Temanggung efforts in the construction of smart city. In this study, the researchers conducted data collection with qualitative methods. Secondary data sourced from the documents of the draft medium-term development (RPJMD), and documents the strategic plan (renstra) of the OPD. In addition, the researchers also conducted focus group discussion with the organisasi perangkat daerah (OPD) in each dimension of the smart city. This research uses Kementerian Komunikasi dan Informatika Smart Readiness Model in the analysis of readiness. Based on the results of data analysis that has been done, the result shows that in general Temanggung Regency has a fairly good readiness, however there are some aspects that need to be improved. So the need for evaluation and improvement to boost the construction of a better future. Keywords—Smart City, Smart Readiness, Analisis Kesiapan, Pemerintah Kabupaten Temanggung